144WS How to Make Judgements About the Quality or Strength of Evidence Transparent. (15th August 2013) - Langendam, M; Mustafa, R; Ventresca, M; Heus, P; Santesso, N; Carrasco, A; Moustgaard, R; Lasserson, T; Schunemann, H
Abstract : Background: When assessing the confidence in intervention effects, i.e. the quality of evidence, guideline developers should make their judgement about this confidence transparent and provide an overall assessment (or grade) of the evidence (GIN & IOM standards 2011). The GRADE approach requires these judgments to be described in comments and footnotes. In a recent review of GRADE evidence summaries, we observed important variability in how guideline developers and authors of Cochrane systematic reviews perform these tasks. Objectives: In this interactive workshop the participants will learn how to formulate understandable and informative reasons for down- and upgrading the quality of evidence by using a footnotes checklist. Target Group: Systematic reviewers and guideline developers assessing the quality or strength of evidence. Description of the Workshop and of the Methods used to Facilitate Interactions: We will present the development of the footnotes checklist. To get hands-on experience the participants will work in large and small groups to: 1) use the checklist on several examples of GRADE evidence profiles and 2) make a judgement about how informative these footnotes are, in particular with guideline panel meetings in mind. The examples will include challenging topics like evidence from single RCT and narrative reviews (no pooled estimates). The outcomes of these exercises will be discussed with the large group and will be used to further improve the checklist.